TCH-043 Stability Study of Sildenafil Capsules by High Performance Liquid Chromatography. (12th March 2013) - Lebecque, M; Beaussart, H; Berneron, C; Odou, P
Abstract : Background: Sildenafil, a phosphodiesterase V inhibitor, is used in paediatrics to treat pulmonary arterial hypertension. However no paediatric formulation was available until a recent launch announced a powder for oral suspension. Purpose: To determine the stability of sildenafil capsules for paediatric dilutions. A HPLC assay has been developed for this purpose. Materials and Methods: The sildenafil dosing method, developed from a previously published method1, is a reverse phase HPLC with UV detection at 240 nm. The column is a C18, the mobile phase composition is acetonitrile/ammonium acetate 0.2 M (50/50) with a flow set at 1 mL/min. Linearity and precision cheques (repeatability and intermediate precision) have been performed to validate the method. Capsules of 1 mg, 5 mg and 10 mg (of sildenafil base) were prepared with sildenafil citrate and corn starch. Samples wer kept at ambient temperature in transparent blister packs sealed with aluminium foil. Uniformity of mass was verified at D0. The visual appearance of the capsules, sildenafil concentrations and chromatographic profiles were checked at D0, D7, D14, D21, D35, D42, D56 and D70. Results: The method was linear up to 150 mg/mL. Repeatability and intermediate precision were demonstrated (SD < 2%). Uniformity of mass was verified, no change in visual appearance and no additional chromatographic peaks were observed. The percentages of the remaining concentrations of sildenafil in the capsules compared to initial concentrations were higher than 90% at D70. Conclusions: The method has been validated and used in a stability study which demonstrated the stability of sildenafil capsules up to ten weeks under the storage conditions studied. These results led us to apply a shelf life of eight weeks to sildenafil capsules. Reference: Daragmeh N. et al, Determination of sildenafil citrate and related substances in the commercial products and tablet dosage form using HPLC. J Pharm Biomed Anal . 2001;25:483–492 No conflict of interest.